Despers Warms Up for Carnival 2004 - Unknown (Newsday)
Ten-time Panorama champions, WITCO Desperadoes Steel Orchestra, has invited returning players and new players to register at the pan yard for the 2004 season. Desperadoes captured the title of Republic Pan Fiesta Champions at the inaugural competition hosted by Pan Trinbago in October 2003.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Carnival -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago